Methodology Of Using Different Social Forms in Foreign Language Lessons - Shakirova Saida Tukhtajonovna (Genius Journals, 2021)
This article examines the methodology of using various social forms in foreign language classes, in particular, such as individual work, work in pairs, in a small group, frontal work, and teamwork.
Keywords: Social forms of work; individual work; work in pairs; teamwork